(untitled) (Research, Society and Development, 2021)
Animal-assisted activity (AAA) is used as an alternative interaction to traditional therapies, in which the animal is used as a mediator to establish informal relationships for recreational and entertainment purposes. Thus, this study was carried out with the aiming analyzing the interaction between thirteen people diagnosed with mental disorders and the equine species, within the context of activities assisted by animals, in a Basic Health Unit in the city of Pelotas-RS. The activities were divided into two moments: face-to-face meetings using two selected and trained horses, and remote meetings through a digital platform during the COVID-19 pandemic. During the meetings, presences and virtual, patients’ behaviors and reactions and questions about their perceptions of activities were observed. The health team of the Unit and the patients themselves were also part of the evaluations. With this experience, it was possible to observe that the intervention was positive for patients, demonstrating the importance of horses as mediators in the communication and social interaction of participants with psychiatric disorders. Therefore, equine-assisted activity proved to be a potential therapeutic alternative in different mental health services.